2019
DOI: 10.3390/fishes4040051
|View full text |Cite
|
Sign up to set email alerts
|

No Correlation between Endo- and Exoskeletal Regenerative Capacities in Teleost Species

Abstract: The regeneration of paired appendages in certain fish and amphibian lineages is a well established and extensively studied regenerative phenomenon. The teleost fin is comprised of a proximal endoskeletal part (considered homologous to the Tetrapod limb) and a distal exoskeletal one, and these two parts form their bony elements through different ossification processes. In the past decade, a significant body of literature has been generated about the biology of exoskeletal regeneration in zebrafish. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…(173) In fact, regenerated fins are nearly indistinguishable from uninjured fins, as long as the endoskeletal elements (eg, hypurals) are retained during the amputation procedure. (5,(174)(175)(176) Notably, regenerative capacity of the caudal fin is not altered even after repeated amputations. (177) The skeleton of the nonmuscular part of the caudal fin, predominantly used for regeneration studies because of its accessibility, is of dermal origin.…”
Section: The Regenerative Capacity Of the Zebrafish Skeletonmentioning
confidence: 99%
“…(173) In fact, regenerated fins are nearly indistinguishable from uninjured fins, as long as the endoskeletal elements (eg, hypurals) are retained during the amputation procedure. (5,(174)(175)(176) Notably, regenerative capacity of the caudal fin is not altered even after repeated amputations. (177) The skeleton of the nonmuscular part of the caudal fin, predominantly used for regeneration studies because of its accessibility, is of dermal origin.…”
Section: The Regenerative Capacity Of the Zebrafish Skeletonmentioning
confidence: 99%
“…Since the endoskeleton precedes dermal skeleton regeneration, one might predict that this latter capacity is a continuation of the former. However, a recent study showed that the capacity of regenerating the first does not necessarily guarantee dermal skeleton regeneration (Pápai et al, 2019), opening the possibility that different systems regulate the regeneration of both structures. The molecular mechanism underlying dermal skeleton regeneration has been extensively studied in zebrafish and its relevance and latest advances have been discussed recently by Marques et al (2019) and Sehring and Weidinger (2020).…”
Section: Dermal Skeletonmentioning
confidence: 99%